STRATEGI PENAWARAN OBJEK WISATA BERBAHASA INGGRIS DI TOURIST INFORMATION CENTER MALIOBORO YOGYAKARTA - Daraginari, Norma Veliska; Mariasari, Septi (Program Studi Diploma Tiga Bahasa Inggris Fakultas Ilmu Budaya Unsoed, 2021)
Tourist Information Center is a facility that provides specific information about local area, tourism attractive, festival, and service. Malioboro Tourist Information Center has the main purpose of helping and facilitating tourist in carrying out their tourist activities. Tourist Information Center as information center also provides print media as promotional media. The purposes of this artcle are to know how the English offering strategies of tourism object in Yogyakarta through Malioboro Tourist Information Center, and to know the difficulties in using English. The strategy that used by TIC officers in providing tourist attraction offers is to know the wishes of tourists and use print media for travel promotion. The strategy aims to promote tourism to tourists who are interested in visiting tourism in Yogyakarta. The author use interview methods, observation methods and literature review method to search the offering strategies. The obstacles faced by the Tourist Information Center officers in providing tourism objects are language barriers, travel planning obstacles and the limitation of print media